Use of Genetically Encoded Calcium Indicators (GECIs) Combined with Advanced Motion Tracking Techniques to Examine the Behavior of Neurons and Glia in the Enteric Nervous System of the Intact Murine Colon - Hennig, Grant W.; Gould, Thomas W.; Koh, Sang Don; Corrigan, Robert D.; Heredia, Dante J.; Shonnard, Matthew C.; Smith, Terence K. (Frontiers in Cellular Neuroscience, 2015)
Genetically encoded Ca2+ indicators (GECIs) have been used extensively in many body systems to detect Ca2+ transients associated with neuronal activity. Their adoption in enteric neurobiology has been slower, although they offer many advantages in terms of selectivity, signal-to-noise and non-invasiveness. Our aims were to utilize a number of cell-specific promoters to express the Ca2+ indicator GCaMP3 in different classes of neurons and glia to determine their effectiveness in measuring activity in enteric neural networks during colonic motor behaviors. We developed several GCaMP3 mice: 1) Wnt1-GCaMP3, all enteric neurons and glia; 2) GFAP-GCaMP3, enteric glia; 3) nNOS-GaMP3, enteric nitrergic neurons, and 4) ChAT-GCaMP3, enteric cholinergic neurons. These mice allowed us to study the behavior of the enteric neurons in the intact colon maintained at a physiological temperature, especially during the colonic migrating motor complex (CMMC), using low power Ca2+ imaging. In this preliminary study, we observed neuronal and glial cell Ca2+ transients in specific cells in both the myenteric and submucous plexus in all of the transgenic mice variants. The number of cells that could be simultaneously imaged at low power (100-1000 active cells) through the undissected gut required advanced motion tracking and analysis routines. The pattern of Ca2+ transients in myenteric neurons showed significant differences in response to spontaneous, oral or anal stimulation. Brief anal elongation or mucosal stimulation, which evokes a CMMC, were the most effective stimuli and elicited a powerful synchronized and prolonged burst of Ca2+ transients in many myenteric neurons, especially when compared with the same neurons during a spontaneous CMMC. In contrast, oral elongation, which normally inhibits CMMCs, appeared to suppress Ca2+ transients some of the neurons active during a spontaneous or an anally evoked CMMC. The activity in glial networks appeared to follow neural activity but continued long after neural activity had waned. With these new tools an unprecedented level of detail can be recorded from the enteric nervous system (ENS) with minimal manipulation of tissue. These techniques can be extended in order to better understand the roles of particular enteric neurons and glia during normal and disordered motility.